2013
DOI: 10.4103/0973-029x.110732
|View full text |Cite
|
Sign up to set email alerts
|

Leimyosarcoma of the buccal mucosa and review of literature

Abstract: Leiomyosarcoma (LMS) is an uncommon malignant spindle cell tumor of the head and neck region. The occurrence is particularly rare in the buccal mucosa of the oral cavity. It is a rapidly growing tumor with aggressive behavior and poor prognosis. Method: This article presents a rare case of primary leimyosarcoma of the buccal mucosa in a 35 year old female and retrospective analysis of primary oral LMS published in the English literature since past 20 years is done. Diagnosis was confirmed by immunohistochemist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…The differential diagnosis of malignant spindle cell tumors in the head and neck includes spindle cell carcinoma and melanoma; sarcomas to be distinguished include malignant nerve sheath tumor and rhabdomyosarcoma [14]. Due to overlap in histologic features, head and neck sarcomas [24] 35 F Buccal mucosa 1.0 × 1.0 n/r n/a n/a Suarez-Alen et al (2015) [25] 66 F Buccal mucosa 2.0 × 1.0 n/r Surgery 52-ANED Present case (2017) 87 M Buccal mucosa NR n/a n/a n/a may be misdiagnosed or misclassified by the pathologist; one review of head and neck soft tissue sarcomas revealed a change in diagnosis by the pathologist in 33-48% of the cases [10]. Given these difficulties, Dry et al pointed out that some of the previously reported cases that did not perform immunohistochemical studies, may in fact not be of myogenic origin [6].…”
Section: Discussionmentioning
confidence: 99%
“…The differential diagnosis of malignant spindle cell tumors in the head and neck includes spindle cell carcinoma and melanoma; sarcomas to be distinguished include malignant nerve sheath tumor and rhabdomyosarcoma [14]. Due to overlap in histologic features, head and neck sarcomas [24] 35 F Buccal mucosa 1.0 × 1.0 n/r n/a n/a Suarez-Alen et al (2015) [25] 66 F Buccal mucosa 2.0 × 1.0 n/r Surgery 52-ANED Present case (2017) 87 M Buccal mucosa NR n/a n/a n/a may be misdiagnosed or misclassified by the pathologist; one review of head and neck soft tissue sarcomas revealed a change in diagnosis by the pathologist in 33-48% of the cases [10]. Given these difficulties, Dry et al pointed out that some of the previously reported cases that did not perform immunohistochemical studies, may in fact not be of myogenic origin [6].…”
Section: Discussionmentioning
confidence: 99%